Chromosome-Scale Reference Genome of Amphicarpaea edgeworthii: A New Resource for Amphicarpic Plants Research and Complex Flowering Pattern - Song, Tingting; Zhou, Mengyan; Yuan, Yuying; Yu, Jinqiu; Cai, Hua; Li, Jiawei; Chen, Yajun; Bai, Yan; Zhou, Gang; Cui, Guowen (Frontiers in Plant Science, 2021)
Amphicarpaea edgeworthii, an annual twining herb, is a widely distributed species and an attractive model for studying complex flowering types and evolutionary mechanisms of species. Herein, we have generated a high-quality assembly of A. edgeworthii by using a combination of PacBio, 10× Genomics libraries, and Hi-C mapping technologies. The final 11 chromosome-level scaffolds covered 90.61% of the estimated genome (343.78Mb), which is a chromosome-scale assembled genome of an amphicarpic plant. Subsequently, we characterized the genetic diversity and population structure of A. edgeworthii species by resequencing individuals collected from their natural area of distribution. Using transcriptome profiling, we observed that specific phenotypes are regulated by a complex network of light, hormones, and MADS-box gene families. These data are beneficial for the discovery of genes that control major agronomic traits and spur genetic improvement of and functional genetic studies in legumes, as well as supply comparative genetic resources for other amphicarpic plants.